Pengaruh Kualitas Pelayanan Terhadap Loyalitas Pelanggan - Felicia; Nagjudin; Yuliana; Hutabarat, Fauzi Akbar Maulana (Journal of Trends Economics and Accounting Research, 2024)
The aim of this research is to determine the effect of service quality on customer loyalty at PT Cahaya Tiga Samudera, Medan. The author uses associative quantitative research methods. Associative research is a research method that asks questions between 2 or more variables. Service quality is a consumer's evaluation of the suitability between the level of service received and the expectations they have. The data collection technique used by the author in this research was a questionnaire. The sample used was 37 customers of PT Cahaya Tiga Samudera, Medan. The research instrument used was validity and reliability testing. The data analysis technique used is simple linear regression. Based on calculations carried out by the author using the SPSS program application, it turns out that the results of the correlation between service quality and customer loyalty are obtained, which gives an indication that the service quality variable and customer loyalty have a positive and strong relationship. From the R square results, it is found that service quality has an influence on customer loyalty, while the rest is influenced by other factors.